Jesus, the New Testament, and Christian origins: perspectives, methods, meanings - Mitternacht, Dieter; Runesson, Anders; Aune, David Edward (Wm. B. Eerdmans Publishing Co., 2021)
Intro -- Title Page -- Copyright -- Dedication -- Contents -- Foreword by David E. Aune -- Preface -- Abbreviations -- 1 Invitation to Study the New Testament -- Beginnings -- A History of New Testament Research -- The Peculiar Case of Pauline Scholarship and Judaism -- Paths to the Past: On Sources and Methods -- 2 Historical Background and Setting -- From Persians to Romans -- Greco-Roman Religions and Philosophies -- Beliefs and Practices in Second Temple Judaism -- Men, Women, and Power in Ancient Society and the Early Jesus Movement -- 3 The Historical Jesus -- Sources about Jesus -- Which Jesus Are We Speaking About? -- The Origins of Jesus -- The Kingdom of God: The Center of Jesus's Proclamation -- Why Did Jesus's Life End on the Cross? -- 4 The Texts -- The Origins and Transmission of the Texts -- The Gospels and the Acts of the Apostles -- The Pauline Letters -- Catholic Letters, the Letter to the Hebrews, and the Book of Revelation -- 5 The Emergence of Early Christianity -- Jewish Christ Followers and the Emergence of Christianity and Judaism -- Paul, His Assemblies, and His Successors -- Johannine Christ Followers -- Non-Rabbinic Jews and Varieties of Judaism -- Gnosticism and "the Gnostics" -- Diversity and the Struggle for Unity -- 6 Readings -- Approaches to the Text -- How to Do a Historical, Text-Oriented Interpretation of a New Testament Text Passage -- A Historical, Text-Oriented Reading of Matt 8:14-17 -- A Historical-Analogical Reading of Matt 5:3-10 -- How Are Good Deeds Motivated? An Argumentation Analysis of 1 Pet 1:17-19 -- "Am I Now Seeking Human Approval?" A Rhetorical-Epistolary Reading of Gal 1:10 -- Lost and Found: A Narrative-Critical Reading of Luke 15 -- "One New Humanity" (Eph 2:15): A Pauline Tradition and Its Reception History.